PENGARUH PELAKSANAAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN BERDASARKAN PERSEPSI PEMERIKSA PAJAK DAN WAJIB PAJAK (STUDI KASUS PADA KPP PRATAMA BANDUNG CICADAS) - Fajar, Catur Martian (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2013)
ABSTRACTTaxes arethe mainsource ofstate revenuein addition to revenues from oilandnon-oilsources. Thus, the taxis a source of revenue that must bestrategically managed. In thecurrenttaxationliteratureare twotermsin minimizingtaxpayerthe amount of taxpayable, thetax evasion (taxavoidance) and tax evasion (taxevasion). Therefore, the tax auditis one oflaw enforcementeffortsin order to improvetax compliance. This study aims to determine the effect of Tax  Audit Execution Against  Taxpayer Compliance  In  KPP Pratama  Bandung Cicadas. The method used in this study is a quantitative method that is associative causal (cause and effect). Results of analysis based on the perception of Audit and Tax Officers. Results of the analysis based on the perception of tax inspectors produce a correlation coefficient () of 0.781, the  coefficient   of   determination   of   0.610,   and   the   comparison   with   and is , which means that the implementation of significant tax audits  on tax compliance body. Results of the analysis based on the perception of the taxpayer produces a correlation coefficient () of 0.840,  the coefficient of determination equal to 0.705, and the results obtained from the comparison with and is  ,  which  means  that  the  implementation  of   tax  audits  significantly influence Taxpayer compliance. Results of the analysis based on the perception of tax inspectors  and  taxpayers  generate  correlation  coefficient  ()  of  0.758,  the  coefficient  of determination of 0.575, And      comparative results with  and is   ,which means a   significant effect on tax audit tax compliance. Based on the analysis results, it can be concluded that the implementation of the tax audit has a significant effect on the Taxpayer compliance in KPP Pratama Bandung Cicadas. Therefore, the implementation of optimal inspection needs to be done optimally to improve tax compliance. keywords:  implementation  of  tax  audit,  taxpayer  compliance,  tax  inspectors,  corporatetaxpayers